Sistem Informasi Administrasi Persuratan Pada Kantor Kecamatan Semarang Tengah - Alexander Dharmawan (LPPM Poltek ST Paul, 2022)
The development and use of information technology today is very important. Almost all office administration work always uses information technology. Information technology is growing, causing all aspects of human work to always be connected with the development of these technologies. One of the important information technology is a mail administration information system. The purpose of making a mail management information system is to be able to manage mail data so that it is organized and can assist officers in making reports more effective. Currently, there are still some obstacles in archiving letters, such as the recording of letters is still done manually and not all letters are archived properly. For that, we need a system that is able to handle filing letters in storage and searching for a document that is needed in a fast and precise time. This system is built with Bootstrap framework, MySQL database server, PHP 7, HTML, CSS and JavaScript. The web is a system that can load various media including images or text documents in which it uses the Hypertext Transfer Protocol (HTTP). This system was built to be able to manage mail so that letters can be archived properly and the web can be accessed at any time to manage letters as long as they are connected to an internet connection.